Neuroimaging to detect cortical projection of vestibular response to caloric stimulation in young and older adults using functional near-infrared spectroscopy (fNIRS) - Karim, HT (2013)
Functional near-infrared spectroscopy (fNIRS) is a non-invasive and portable neuroimaging technique. The method uses non-ionizing laser light in the range of red to near-infrared to detect changes in cerebral blood oxygenation. In this study, we used fNIRS to investigate cortical hemodynamic changes in the temporo-parietal and frontal regions during caloric vestibular stimulation. Caloric stimulation has previously been investigated using functional magnetic resonance imaging (fMRI) and positron emission tomography (PET), which serves as a validation of the fNIRS imaging modality toward the measurement of vestibular related brain regions. To date, only a single study has used fNIRS during caloric irrigations, which observed blood volume changes in the temporal-parietal area in healthy younger subjects. In this current study, fNIRS was used to measure cortical vestibular activation in 10 right-handed younger subjects (5 male and 5 female, age 25+/−6 years) and 10 right-handed older subjects (6 male and 4 female, age 74 +/−5 years). We investigated both warm (44°C) and cool (30°C) unilateral caloric vestibular stimulation. Consistent with previous reports, we found that warm (44°C) caloric irrigation caused a bilateral activation. In addition, we found that cool (30°C) caloric irrigation caused contralateral activation of the temporo-parietal area. This study is the first to investigate age effects of the caloric stimulation on brain activity. We found that the older subjects had stronger bilateral effects than the younger subjects. Our results confirm previous fMRI and PET studies that showed cortical activation during caloric vestibular irrigation is dependent on side of irrigation, and temperature of irrigation. Furthermore, our results demonstrate that fNIRS is a viable technique in measuring cortical effects during vestibular tasks.